A PRAGMATICS ANALYSIS OF WARNING UTTERANCES ON COMPUTER’S GAME (ZUMA’S REVENGE) - SEPTANTIA , AMALIAH MUSTIKA (2011)
This research deals with warning utterances in Zuma’s Revenge computer’s game. The research is aimed at describing sentence type and pattern, implicature and politeness strategies of warning utterances on computer’s game ( Zuma’s Revenge). The researcher employs the descriptive qualitative as the type of the research. The data source of this research is the game Zuma’s Revenge. In collecting the data, the writer uses documentation method and the steps are playing the game of Zuma’s Revenge, taking note of sentences containing warning utterances, l isting the data that are collected, and coding the data. The techniques of analyzing data of this research are describing the sentence type by referring to grammatical rules, analyzing the implicature based on context of pragmatics’ theory, and illuminating the politeness strategies by using the theory of politeness. The result of the study shows that first, the sentence types of warning utterances are: exclamatory sentence, declarative sentence, imperative sentence, and interrogative sentence. The sentence pattern that is mostly used is Subject + Predicate followed by Complement. Second, the implicature of warning utterances covers conventional and conversational implicature. Third, the politeness strategies of warning utterances are: bald on record, positive politeness, and negative politeness strategy.